Experience and its role in proving the administrative procedure - عبود صعب ناجي; علي عمار حسين (Journal of Legal Sciences, 2019)
Experience is no longer the only means of judicial proceedings. That’s why. The examination of the issue of experience in the less important than its role in extending the aid and assistance to the judge, and the role in the tasks of lawsuits in which the experience is evidence of the evidence, the Secretary and fundamental to resolve the existing dispute and the separation of the case on the basis of experience. It seems that the judges have been presented in the lawsuit from the limits of the science of law and his perceptions can not be explained in fact? What came in the act of this experience by the expert concerned.